Pengaruh Sustainability Report dan Profitabilitas terhadap Nilai Perusahaan Pada Perusahaan Subsektor Energi - Aisyah Ramalia; Cherrya Dhia Wenny (MDP Student Conference, 2026)
Abstract:This study aims to examine the impact of Sustainability Reports (X1) and Profitability (X2) on Firm Value (Y) in energy subsector companies listed on the Indonesia Stock Exchange during the period 2021 to 2024. In this study, the approach used is quantitative by utilizing secondary data taken from annual reports and corporate sustainability reports. The sample determination was carried out using a purposive sampling method. Sustainability Reports are measured using the Sustainability Report Disclosure Index (SRDI), Profitability is measured based on Return on Assets (ROA), and Firm Value is evaluated using Price to Book Value (PBV). Data analysis for this study was carried out through multiple linear regression methods using SPSS software. The results of the analysis show that Sustainability Reports and Profitability have a positive impact on Firm Value. This finding suggests that companies that present sustainability information more clearly and have good profit performance tend to receive higher ratings from investors. Therefore, regular management of sustainability reports and achieving good financial performance are very important in increasing market confidence and strengthening company value, especially for companies operating in the energy sub-sector.